New combinations in the fern family Equisetaceae - Kessler, Michael (Phytotaxa, 2025)
Equisetaceae Rich. ex DC. in Lamarck & de Candolle (1805: 49) is an ancient fern family sister to all other ferns (Pryer et al., 2001; Knie et al., 2015). The about 18 extant species are traditionally divided into the two subgenera Equisetum Linnaeus (1753: 1061) and Hippochaete (Milde 1865: 298) Baker (1887: 3), mainly based on stomata position, stem persistence, and strobilus structure (Milde, 1861). Recently, it has been found that Equisetum bogotense Kunth in Humbold, Bonpland & Kunth (1815: 42), which had long been considered to be a member of subgenus Equisetum, is sister to all other species of the genus, based on both morphological (Elgorriaga et al., 2018) and molecular evidence (Christenhusz et al., 2019). Equisetum bogotense shares numerous plesiomorphic characters such as superficial stomata with a scattered arrangement, non-apiculate strobili, and persistent leaf teeth with members of subgenus Equisetum, but differs by having filamentous, strictly unisexual gametophytes, whereas all other species have thalloid gametophytes that can be uni- or bisexual (Hauke, 1967, 1968, 1969, 1977; Duckett 1973). The evolutionary line leading to E. bogotense diverged from all other extant species about 175 mya, with Equiseum and Hippochaete separating from each other about 135 mya (Christenhusz et al., 2021). To account for the isolated phylogenetic position of E. bogotense, Christenhusz et al. (2019) described subgenus Paramochaete Christenhusz & Husby (2019: 326).